Reliability and validity indices of the UPSEC process test - Guirey, Evelyn Ganzon 1948- (1975)
The aim of this study was to estimate the reliability and validity indices of the UPSEC Test, so that on further use, this test will offer results which are more dependable of student's general skills and achievement in science. Thus, it serves as an evaluation of the effectiveness of the Science Education Center curriculum materials.
Thesis (M.A.T.)--University of the Philippines, Quezon City.
Keywords: University of the Philippines -- Science Education Center -- Process Test. -- Quezon City; Science -- Ability testing